STUDI FENOMENOLOGI: PENGALAMAN KELUARGA DALAM MENDAMPINGI PASIEN SAAT PROSES RESUSITASI DI INSTALASI GAWAT DARURAT RSUD Dr. SAIFUL ANWAR MALANG - Kristina Pae; Sri Andarini; Retno Lestari (Fakultas Ilmu Kesehatan, 2015)
The services for critically ill patient in emergency department focus to save the life of patient with resuscitation, stabilization, and monitoring of the patient's condition. Family who have family members in critical condition have a need to be close to patient. Family needs to be able to see the patient, to take a care for patient and providing support to patient who are in critical condition. This study is a qualitative research with phenomenological approach. The aim of this study was to explore the family experience when they presence during resuscitation. The study was conducted at ED of Dr. Saiful Anwar Hospital Malang. There are 6 participants were selected based on inclusion criteria that have been set. Data were collected through in-depth interviews method. The data saturation of the participants obtained if nothing else is bring new themes via the data submitted. Results were analyzed using data analysis Braun and Clark. Transcripts of the interviews were analyzed using qualitative analysis. This research identified five themes, they are (1) anxiety when FPDR, (2) familybecomesstronger, (3) familywishtocontinue the FPDR process, (4) loveandroleas a motivation to do FPDR, (5) the complexity ofadversityin FPDR. Based on the results of this study, author expected that direction of hospital can began to consider the development of FPDR service so family able to prepare themselves with the grieving process that will occur and patients canpassedin peace. Keywords: Family, Presence, Resucitation